Studi Makna Teks Bahasa Arab dalam Teori Kontekstual/Study of the Meaning of Arabic Texts in Contextual Theory - Zulkiflih Zulkiflih; Fitria Fitria (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2023)
This study aims to determine the meaning of an Arabic text through a Contextual theory approach. This study uses library research where data is collected through literature, books, journals and scientific articles. The results of this study are that contextual theory is very relevant in the process of interpreting an Arabic text. There are four things that can be used to understand a text in contextual theory, namely: linguistic context by looking at the basic pronunciation of a text, emotional context by looking at a text from a sense perspective, context of situations and conditions paying more attention to a meaning by looking at the situation and condition of a text, and this Socio-cultural context emphasizes aspects that occur in society in relation to the context of a meaning. Abstrak: Penelitian ini bertujuan untuk mengetahui makna suatu teks bahasa Arab melalui pendekatan teori Kontekstual. Penelitian ini menggunakan penelitian kepustakaan yang datanya dikumpulkan melalui literatur, kitab-kitab, jurnal dan artikel ilmiah. Adapun hasil dari penelitian ini adalah teori kontekstual sangat relevan dalam proses penafsiran suatu teks arab. Ada empat hal yang dapat digunakan untuk memahami suatu teks dalam teori kontekstual, yaitu: konteks kebahasaan dengan melihat dasar lafadz suatu teks, konteks emosional dengan melihat suatu teks pada perspektif rasa, konteks situasi dan kondisi lebih memperhatikan suatu makna dengan melihat situasi dan kondisi suatu teks, dan konteks Sosio-kultural ini lebih mengedepankan aspek yang terjadi di masyarakat kaitannya dengan konteks suatu makna.